2017
DOI: 10.1055/s-0037-1599276
|View full text |Cite
|
Sign up to set email alerts
|

Endolymphatic Sac Surgery for Ménière's Disease – Current Opinion and Literature Review

Abstract: Introduction The endolymphatic sac is thought to maintain the hydrostatic pressure and endolymph homeostasis for the inner ear, and its dysfunction may contribute to the pathophysiology of Ménière's disease. Throughout the years, different surgical procedures for intractable vertigo secondary to Ménière's disease have been described, and though many authors consider these procedures as effective, there are some who question its long-term efficacy and even those who think that vertigo control is achieved more d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…While these techniques are considered nondestructive procedures as they preserve the auditory function, transmastoid labyrinthectomy is completely destructive to the labyrinth and is indicated only in patients with established nonserviceable hearing loss and persistent recurrent vertigo attacks. [106][107][108][109][110][111][112] -Vestibular rehabilitation: It could be proposed in patients with MD with an established vestibular deficit to facilitate vestibular compensation. However, in the initial years of the disease, its usefulness is controversial.…”
Section: Treatmentmentioning
confidence: 99%
“…While these techniques are considered nondestructive procedures as they preserve the auditory function, transmastoid labyrinthectomy is completely destructive to the labyrinth and is indicated only in patients with established nonserviceable hearing loss and persistent recurrent vertigo attacks. [106][107][108][109][110][111][112] -Vestibular rehabilitation: It could be proposed in patients with MD with an established vestibular deficit to facilitate vestibular compensation. However, in the initial years of the disease, its usefulness is controversial.…”
Section: Treatmentmentioning
confidence: 99%
“…Moreover, the study at hand depicts detailed pre- and postoperative audiometric and vestibular results showing the safety of this non-destructive treatment option for MD patients. All patients received the same type of endolymphatic sac surgery—a endolymphatic mastoid shunt with application of a triangular silicone foil which seems to be the most common technique according to the literature [ 28 – 30 ] (Table 4 ). The most crucial novel aspect of the study at hand is the comparison of results between both study subgroups: patients who seem to have benefitted from the procedure and those who have not.…”
Section: Discussionmentioning
confidence: 99%
“…Other interventions for MD like endolymphatic sac surgery were developed around the same time and are still offered to patients. Many case series by prominent otologic surgeons have shown excellent rates of improvement in vertigo and described variations of this technique (8). In 1981, however, one of the few placebo-surgery controlled double-blind studies in the medical literature by Thomsen et al showed reductions in symptoms (even after re-examination 3 years after surgery) (9) in all patients, regardless of whether they underwent endolymphatic sac decompression or shunting versus simple mastoidectomy (10).…”
Section: History Promotes Critical Awareness Of How Our Current Think...mentioning
confidence: 99%